#TITLE_ALTERNATIVE# - SATRIA MULYADI (NIM : 22309012), DIKDIK
Unexploded Ordnance (UXO) are explosives that can be dangerous for human. Presence of UXO in an area makes the area unsafe for human activities. Therefore, detection of UXO must be done to clean up the area to be used for various activities. One of geophysical methods that can be used to detect UXO is magnetic method. In this study, modeling of magnetic data was carried out for detection of UXO. A UXO is assumed as a magnetic dipole. This assumption is then used in forward modeling and inversion modeling to find the location of UXO. Search for a solution to the inversion modeling was performed by the method of systematic and random search. The solution is obtained by evaluating the value of an objective function which is the quadratic difference between the field data and model response of UXO. Model that produces the minimum objective function value is the solution. Solutions obtained using the method of systematic and random search showed are relatively similar. The best solution for both methods lies about 0.1 m from the actual location of UXO.